2018
DOI: 10.1002/star.201800100
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion Complexes of Non‐Granular Maize Starch with Fatty Acids and Ibuprofen. A Comparative Study of Their Morphology and Structure

Abstract: Drum dried pregelatinized normal maize starch complexes with fatty acids (decanoic, myristic, palmitic, stearic, and oleic acid) and ibuprofen are studied by various techniques. The aim of the study is to investigate the structural and morphological characteristics of the starch complexes and assess whether any differences might exist between the starch‐fatty acid systems and the starch‐ibuprofen system. The complexes are prepared at 30, 50, or 70 °C. X‐ray diffraction analysis reveals the semicrystalline V‐ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 36 publications
(70 reference statements)
1
9
0
Order By: Relevance
“…Moreover, the diffractograms of wheat starch-palmitic acid complexes revealed three extra peaks at 7.2 , 21.3 , and 24 attributed to the presence of fatty acid crystals. 19 All the complexes except 0.5 h had no signicant change in the V-type peak intensity. It indicated that prolonging treatment time had little effect on the crystalline structure of the complexes aer the particle structure was destroyed.…”
Section: Crystalline Structurementioning
confidence: 91%
“…Moreover, the diffractograms of wheat starch-palmitic acid complexes revealed three extra peaks at 7.2 , 21.3 , and 24 attributed to the presence of fatty acid crystals. 19 All the complexes except 0.5 h had no signicant change in the V-type peak intensity. It indicated that prolonging treatment time had little effect on the crystalline structure of the complexes aer the particle structure was destroyed.…”
Section: Crystalline Structurementioning
confidence: 91%
“…Nowadays, a considerable amount of research has been devoted on the interaction between amylose and bioactive compounds with therapeutic properties. Drugs such as ibuprofen, [ 22–24 ] nimesulide, [ 25 ] and indomethacin [ 26,27 ] have been studied and the results indicated that the amylose complexes are rather stable in the simulated gastric fluid and they can promote the drug release from complexes in the simulated intestinal fluid.…”
Section: Introductionmentioning
confidence: 99%
“…Another very promising method, which still waits to be utilized by the industry, is the formation of molecular inclusion complexes of amylose with various ligands. Amylose, the essentially linear component of starch, is well known to possess the unique property among the biopolymers to form helical inclusion complexes with a substantial number of polar and non‐polar compounds such as long chain fatty acids, fatty alcohols, monoglycerides, various volatile flavors such as terpenes, and certain drugs such as ibuprofen . Since starch is abundant in nature, easily available and cheap, it seems to be an ideal raw material for use as a microcarrier of bioactive compounds.…”
Section: Introductionmentioning
confidence: 99%